Comparative analysis of blockchain adoption in the public and private sectors. A technology-organization-environment (TOE) framework approach - Benchiș, Melisa Petra; Shahzad, Khuram; Dan, Sorin (Elsevier, 2025)
Blockchain technology (BT) can potentially enhance transparency, efficiency, and trust across all domains. However, it remains unclear how the relative adoption of BT between the private and public sectors compares in light of existing studies. This article contributes to the literature by evaluating the adoption process through the technology, organizational, and environmental dimensions of the TOE framework. A comparative research design was employed through 21 semi-structured interviews with participants from the public and private sectors in Finland. The results indicate that challenges to adoption uniformly exist between both sectors in the form of regulatory concerns and misconceptions regarding energy matters, as well as incentives that are directly linked to the sector. The private sector is incentivized to adopt BT for scalability, efficiency, and responsiveness to market demand in light of competitive advantage. The public sector is motivated to adopt BT through transparency and regulatory concerns, although a willingness to accommodate legacy systems in the short term exists so that public services and activities are not interrupted. In addition, our findings highlight the important role of public institutions in BT adoption. Ultimately, both sectors require strong visionary leadership and training to overcome knowledge deficiencies and proof-of-concept studies to reduce uncertainty and reliance on external applications and partnerships. This article contributes to the literature by comparatively highlighting the similarities and differences in this phenomenon. It offers practical and policy-related implications and encourages an industry-specific approach to adoption, cross-industry innovations, and regulatory policies.
Keywords: Blockchain adoption; TOE framework; Comparative analysis; Technology-organization-environment; private sector; public sector; fi=Julkisjohtaminen|en=Public Management|; fi=Tuotantotalous|en=Industrial Management|